Rudolf Schlechter's South-American orchids III. Schlechter's "network": North and Northeast Brazil, The Guianas - Ossenbach, Carlos (Universidad de Costa Rica, 2020)
The third chapter of the series about Rudolf Schlechter’s South-American orchids presents concise biographical information about those botanists and orchid collectors who were connected to Schlechter and worked in north and northeastern Brazil, as well as in the three Guianas. As an introduction, a brief geographical outline is presented, dividing the northern territories in four zones: the Amazon basin, the Araguaia-Tocantins river basin, the Northeast region and the Guianas. It is followed by a short mention of the historical milestones in the history of orchids in these regions during the preceding centuries. Key words: Amazon River, biography, history of botany, Orchidaceae, Roraima, Tocantins River